The response of wages and actual hours worked to the reduction of standard hours in Germany - Jennifer Hunt (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
A transformation of what had become a universal 40 hour standard work week in Germany began in 1985 with reductions negotiated in the metal-working and printing sectors. These reductions have continued through 1995, and were followed by reductions in other sectors. Using data from the German Socio-Economic Panel, I find that increased overtime or reduced short time was little used to offset the reduction in standard hours: a one hour reduction in standard hours appears to have translated into a reduction in actual hours worked of between 0.85 and 1 hour for workers in manufacturing. One might expect this to result in a loss of earnings for workers in affected industries. However, I substantiate the union claim of "full wage compensation": reductions in standard hours were accompanied by a relative rise in the hourly straight-time wage of 2-3 % for each hour fall in standard hours, enough to keep monthly earnings the same as in unaffected industries.
Keywords: 330; Arbeitszeitgestaltung; Lohn; Arbeitszeit; Deutschland